2010
DOI: 10.1155/2010/927601
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and In Vitro Antimicrobial, Anthelmintic and Insecticidal Activities Study of 4(4′‐Bromophenyl)‐6‐substituted‐aryl‐1‐acetyl pyrimidine‐2‐thiols

Abstract: A new series of 4(4'-bromophenyl)-6-substituted aryl-1-acetyl pyrimidine-2-thiol derivatives were synthesized by heating chalcones with thiourea, in the presence of ethanolic potassium hydroxide, followed by treatment with acetyl chloride. The structure of the compounds was characterized by IR and H1NMR spectral study and elemental analysis. The compounds were screened for their antimicrobial, anthelmintic and insecticidal activities. All the compounds exhibited significant to moderate biological activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…A relationship between dependent and independent variables (biological activities and physicochemical descriptors, respectively) was resolved statistically using regression analysis [14]. Linear regression is reached by fitting a best-fit straight line to the data using the least squares method.…”
Section: Multiple Linear Regression Methodsmentioning
confidence: 99%
“…A relationship between dependent and independent variables (biological activities and physicochemical descriptors, respectively) was resolved statistically using regression analysis [14]. Linear regression is reached by fitting a best-fit straight line to the data using the least squares method.…”
Section: Multiple Linear Regression Methodsmentioning
confidence: 99%
“…A new series of 4(4′-bromophenyl)-6-substituted aryl-1-acetylpyrimidine-2-thiol derivatives were synthesized and screened for the in vitro antimicrobial activity. The results showed that all the synthesized compounds ( 154 ) have shown significant, good to moderate antimicrobial activity due to the presence of thio group, which enhanced the respective activities with varied substituent groups, against selected pathogens [ 165 ]. Trantolo et al synthesized a series of N 6 -substituted 6-aminopyrimidines and examined the effects of substituents governing the inhibition of DNA polymerase Ι Ι Ι from B. subtilis.…”
Section: In Vitro Antimicrobial Activity Profilmentioning
confidence: 99%